Dokumenty i materiały Towarzystwa Muzycznego im. M. Łysenki oraz Wyższego Instytutu Muzycznego w zbiorach muzeum Stanisława Ludkiewicza we Lwowie - Horak, Jakym (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2021)
The article deals for the first time withM. Lysenko Music Society & Higher Music Institute’s records in the collection of Stanislaw Lyudkevych Museum in Lviv. The museum collection includes sections of photographic archive, documents and memorabilia of M. Lysenko Music Society, archived orchestral scores, the educational curriculum and studies of the Music Society Board, yearly andquarterly archives, belles lettres that belonged to theHigher Music Institute and Music Society,and the teachersand students’ personal appeal letters to S. Lyudkevych when he was a Head of Board. The list of memorabilia letters and evidence reports is in the appendix. The Museum Archive is the principal repository of documents and memorabilia letters, which were only partially available in formerscientific archives.